2019
DOI: 10.5937/leksir1939005c
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of antioxidant and hepatoprotective potential of Satureja montana extracts against CCl4 induced liver damage

Abstract: The influence of Satureja montana extracts on several liver biochemical parameters in mice administered with carbon tetrachloride was estimated. In vivo investigation of antioxidant properties of S. montana extracts encompassed monitoring of biochemical parameters (derived from liver homogenate and blood hydrolyzate) and examination of potential hepatoprotective effect after intoxication with carbon tetrachloride. Biochemical tests included determination of activity of several antioxidant enzymes: xanthine oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Additionally, Table 3 contains values of biochemical parameters of oxidative stress measured in the control group that was treated with distillated water and in groups that were treated only with SC1 and SD1 extracts [36]. By comparing these values with the parameters of oxidative stress determined in this study, it can be concluded that extracts exhibit selectivity towards tumor cells by inducing them into oxidative stress, while not manifesting any side-effects on the healthy cells.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Additionally, Table 3 contains values of biochemical parameters of oxidative stress measured in the control group that was treated with distillated water and in groups that were treated only with SC1 and SD1 extracts [36]. By comparing these values with the parameters of oxidative stress determined in this study, it can be concluded that extracts exhibit selectivity towards tumor cells by inducing them into oxidative stress, while not manifesting any side-effects on the healthy cells.…”
Section: Discussionmentioning
confidence: 88%
“…Table 3. Biochemical parameters of control group and the groups treated with the SD1 and SC1 extracts [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although after the pretreatment carvacrol content was increased by 25%, the total antioxidant response of the extracts was lowered [ 22 ]. Additionally, in in vivo studies where S. montana extracts with significantly different content of extracts were administered, it was observed that antioxidant properties of extracts with a higher content of carvacrol were not pronounced [ 72 , 73 ]. Therefore, carvacrol is not the main carrier of antioxidant activity of the extracts, but the properties of the extracts are a consequence of possible synergistic and antagonistic effects of all constituents.…”
Section: Resultsmentioning
confidence: 99%